Modeling the mudslide aftermath of the 2007 Southern California Wildfires - Ren, Diandong; Fu, R.; Leslie, Lance; Dickinson, R. (Springer Netherlands, 2011)
An investigation is made of the influence of fire-caused deforestation on precipitation- triggered, shallow landslide susceptibilities in southern California, using a scalable and extensible geo-fluid model (SEGMENT), that accounts for soil mechanics, root distribution, and relevant hydrologic processes. SEGMENT is applicable to variable regional topography, soil thickness profiles, and vegetation coverage. In this study, for southern California following the 2007 wildfires, three experiments were performed with rainfall recurrence periods chosen to be 2, 10, and 25 years. These intervals correspond to 24-h storm rainfall totals of 17, 25.4, and 33 mm. The model generated landslide stability maps that identified three areas of high instability. These unstable regions are located in the San Fernando Valley, the San Gabriel Mountains, and the Santa Monica Mountains. In each case, the vegetation cover had been severely burned during the preceding 2007 wildfires. The model results showed that burning from wildfires is a major destabilizing factor for southern California. Burn sites are more prone to landslides than vegetated slopes because the soil more readily exceeds its critical moisture content. Severe droughts in a future warming climate are expected to increase the likelihood of more frequent and intense wild fires. Higher temperatures combined with decreased total rainfalls facilitate more intense landslides, including devastating mudslides, following heavy precipitation. Finally, the model is designed to assist in developing timely mitigation measures for postfire, storm-triggered landslides.